Innovative Techniques for Teaching English in Elementary Schools: Perspectives from Young Learner Educators - Muhammad Dalimunte; Sholihatul Hamidah Daulay; Afanin Nabila; Ahmad Husein Nst (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2025)
English is one of the most important languages needed nowadays. English has been introduced to children since childhood. An English teacher must be able to teach English to the children he teaches. The purpose of this study is to find out what techniques are used by teachers in teaching English to children in Indonesia. The method used by the author in this study is a literature review. This method uses several journals or books and then summarizes the results found in the journal and book collections. The results of this study indicate that the techniques often used by teachers to teach English to children in Indonesia include learning with games and songs.